KEBIJAKAN DAN STRATEGI PERTAHANAN INDONESIA (Studi Kasus Konfl ik Di Laut Cina Selatan) - Prabowo, E. Estu (Jurnal Ketahanan Nasional, 2013)
This paper explained Indonesia policy and strategy defenseâs with the South China Sea conflict case study. The data qualitative showed Indonesia defenseâs policy and strategy to anticipated South China Sea conflict had not yet well formulated. The defenseâs policy and strategy had not yet in the same direction as the foreign countryâs policy which gave special attention to the Southeast Asia regionâs dynamic, including South China Sea. Therefore the present defenseâ strategy and policy had not yet given attention to the South China Sea conflict dynamic. Indonesia defenseâs policy and strategy now considered South China Seaâs conflict able to solved with soft power and do not anticipate the hard power use which would affect the Indonesiaâs national need.Keywords: Policy, Strategy, Indonesiaâs Defense, Confl ict, South China Sea.